Parental psychological control, autonomy frustration, and psychological well-being among boarding school adolescents - Zahrah Aulianissa Manindjo; Vidya Anindhita; Fitri Ariyanti Abidin (Intelektual Pustaka Media Utama, 2023)
Psychological well-being is fundamental for adolescents to be adaptive and fully functioning in the environment. For adolescents who stay in boarding school, even though they are away from their parents due to boarding school rules, parents still have a role to provide support and direct their behavior through parental control. On the other hand, adolescence is a period where children learn to be detached from their parents and strive for autonomy. The present study aimed to investigate the role of autonomy need frustration as a mediating variable between parental psychological control and psychological well-being for adolescents who stayed in boarding school. A survey was completed by 318 Islamic boarding school adolescents with an age range from 12–18 years old. The findings showed that autonomy need frustration fully mediated the relationship between parental psychological control and psychological well-being. Parental psychological control causes a decline in boarding school adolescents’ psychological well-being through the feeling of autonomy need frustration. These results support further development of studies regarding the psychological well-being of adolescents, especially in the boarding school context.